The planning and design of a multimedia courseware on UNIMAS online learning system - Stephen, Ting Pink Lik (Universiti Malaysia Sarawak, UNIMAS, 2009)
With the emerging advances in technology, Universiti Malaysia Sarawak (UNIMAS) at present has deployed an online learning system known as Morpheus system to enable the integration of technology into the instructions that aim to enrich the teaching and learning efficiency. However, the current face-to-face training sessions on this online learning system for the UNIMAS academic staff poses some limitations. To overcome these limitations, this project was conducted to plan and design a multimedia courseware (known as ‘Mastering Morpheus’) as an avenue to guide these lecturers in learning the Morpheus system. The planning and design phases employed in this project were based on the ‘Model for Design and Developmen’ proposed by Alessi and Trollip (2001). According to the feedbacks and comments obtained from both instructional design and subject matter experts as well as three potential learners, some changes and the corresponding revisions had been made accordingly to further improve the completeness and quality of the courseware. In conclusion, the results of the evaluation indicated that the potential learners were generally satisfied with the overall presentation and quality of the courseware.